Uczniowskie doświadczenia pozaliterackie w procesie poznawania dzieła literackiego = Pupil's Extraliterary Experiences in the Process of a Literary-Work-of-Art Cognition - Zielińska, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The following work shows an attempt to modificate the theory of systemic teaching and learning literature. The author in accord with the recommendations of modern psychologists, educationalists and literature didacticians pertain to maintaining close relations between life and school, provides for their particularization in the field of literature didactics.
Keywords: dzieło literackie; dydaktyka literatury; młodzież